Geometrical enhancement of planar loop antennas for inductive near-field data links - Eteng, Akaa Agbaeze (Institute of Electrical and Electronics Engineers (IEEE), 2015)
The low Q-factor requirements of High-Frequency Radio Frequency Identification (HF-RFID) interrogator antennas constrain transmission performance when they are used in data links requiring similar terminal antennas. This letter presents a geometrical approach to enhance the transmission performance of planar loop antennas without a significant change to their standalone performance as HF-RFID interrogator antennas. The method distributes the turns of a modified planar square loop antenna to enhance the coupling level in a symmetric link, while limiting the change in Q-factor from a conventional HF-RFID interrogator antenna. Results from a presented test case show that the design method enables a 5.75% increase in peak transmission coefficient, and a 28.42% fractional bandwidth increase in a symmetric link, compared to a conventional design